Chronic use of PAH‐specific therapy in World Health Organization Group III Pulmonary Hypertension: a systematic review and meta‐analysis. (1st March 2017) - Prins, Kurt W.; Duval, Sue; Markowitz, Jeremy; Pritzker, Marc; Thenappan, Thenappan
Abstract : Pulmonary hypertension (PH) complicating chronic obstructive pulmonary disease (COPD‐PH) and interstitial lung disease (ILD‐PH) (World Health Organization [WHO] Group III PH) increases medical costs and reduces survival. Despite limited data, many clinicians are using pulmonary arterial hypertension (PAH)‐specific therapy to treat WHO Group III PH patients. To further investigate the utility of PAH‐specific therapy in WHO Group III PH, we performed a systematic review and meta‐analysis. Relevant studies from January 2000 through May 2016 were identified in the MEDLINE, EMBASE, and COCHRANE electronic databases and www.clinicaltrials.gov . Change in six‐minute walk distance (6MWD) was estimated using random effects meta‐analysis techniques. Five randomized controlled trials (RCTs) in COPD‐PH (128 placebo or standard treatment and 129 PAH‐medication treated patients), two RCTs in ILD‐PH (23 placebo and 46 treated patients), and four single‐arm clinical trials (50 patients) in ILD‐PH were identified. Treatment in both COPD‐PH and ILD‐PH did not worsen hypoxemia. Symptomatic burden was not consistently reduced but there were trends for reduced pulmonary artery pressures and pulmonary vascular resistance with PAH‐specific therapy. As compared to placebo, 6MWD was not significantly improved with PAH‐specific therapy in the five COPD‐PH RCTs (42.7 m; 95% confidence interval [CI], –1.0 – 86.3). In the four single‐arm studies in ILD‐PH patients, there was a significant improvement in 6MWD after PAH‐specific treatment (46.2 m; 95% CI, 27.9–64.4), but in the two ILD‐PH RCTs there was not an improvement (21.6 m; 95% CI, –17.8 – 61.0) in exercise capacity when compared to placebo. Due to the small numbers of patients evaluated and inconsistent beneficial effects, the utility of PAH‐specific therapy in WHO Group III PH remains unproven. A future clinical trial that is appropriately powered is needed to definitively determine the efficacy of this widely implemented treatment approach.